Chemical Profiling and Assessment of Antineurodegenerative and Antioxidant Properties of Veronica teucrium L. and Veronica jacquinii Baumg. - Živković, Jelena (2018)
Neuroprotective potential of V. teucrium and V. jacquinii methanol extracts was analyzed. Chemical analysis of investigated extracts showed the presence of phenolic acid derivatives, flavonoids and one secoiridoid. The detected flavonoids derived from flavones (luteolin and isoscutellarein in V. jacquinii; apigenin, isoscutellarein and luteolin in V. teucrium) and flavonol (quercetin in V. jacquinii). Acteoside was the dominant compound in V. jacquinii, while plantamajoside and isoscutellarein 7-O-(6â€´-O-acetyl)-ß-allosyl (1â€´?2â€´)-ß-glucoside were the major phenolics in V. teucrium. Additionally, the antineurodegenerative activity was tested at concentrations of 25, 50, and 100 µg/ml using acetylcholinesterase (AChE) and tyrosinase (TYR) assays. The inhibition of both enzymes was achieved with the investigated extracts, ranging from 22.78 to 35.40% for AChE and from 9.57 to 16.38% for TYR. There was no statistical difference between the activities of the analyzed extracts. Our data indicate that V. teucrium and V. jacquinii may have beneficial effects against Alzheimer's and Parkinson's disease.